The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1097/hep.0000000000000306
|View full text |Cite
|
Sign up to set email alerts
|

The road to pandemic recovery: Tracking COVID-19’s impact on cirrhosis care and outcomes among 111,558 Veterans

Abstract: Background & Aims: This study aimed to evaluate quarterly trends in process and health outcomes among Veterans with cirrhosis and assess the factors associated with cirrhosis outcomes before and during the COVID-19 pandemic. Approach & Results: US Veterans with cirrhosis were identified using the Veterans Health Administration Corporate Data Warehouse. Quarterly measures were evaluated from September 30, 2018, through March 31, 2022, including twice yearly screening for hepatocellular carcinoma (HCC-6), new … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 61 publications
(115 reference statements)
1
1
0
Order By: Relevance
“…Most clinicians reported that patients with cirrhosis often missed appointments and HCC surveillance was delayed due to limitations of in-person visits. These observations confirm existing reports and concerns about the long-term outcomes of delays in cirrhosis care following onset of the COVID-19 pandemic . However, even more concerning, among survey respondents in the current study, it is clear that despite being over 3 years post onset of the pandemic, the disruptions in cirrhosis care and HCC surveillance in particular remain, and most respondents do not have an effective mechanism to track and re-engage patients who missed HCC surveillance during the pandemic.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Most clinicians reported that patients with cirrhosis often missed appointments and HCC surveillance was delayed due to limitations of in-person visits. These observations confirm existing reports and concerns about the long-term outcomes of delays in cirrhosis care following onset of the COVID-19 pandemic . However, even more concerning, among survey respondents in the current study, it is clear that despite being over 3 years post onset of the pandemic, the disruptions in cirrhosis care and HCC surveillance in particular remain, and most respondents do not have an effective mechanism to track and re-engage patients who missed HCC surveillance during the pandemic.…”
Section: Discussionsupporting
confidence: 74%
“…These observations confirm existing reports and concerns about the long-term outcomes of delays in cirrhosis care following onset of the COVID-19 pandemic. [33][34][35] However, even more concerning, among survey respondents in the current study, it is clear that despite being over 3 years post onset of the pandemic, the disruptions in cirrhosis care and HCC surveillance in particular remain, and most respondents do not have an effective mechanism to track and re-engage patients who missed HCC surveillance during the pandemic. This is particularly concerning given that populations who use safety-net health systems have already experienced barriers in timely access to health care even before the onset of the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 72%